Examining genetic counselors' implicit attitudes toward disability. Issue 6 (23rd August 2019) - Gould, Helen; Hashmi, Syed S.; Wagner, Victoria F.; Stoll, Katie; Ostermaier, Kathryn; Czerwinski, Jennifer
Abstract: Genetic counselors have a unique role in healthcare that requires a balance between being a patient educator and patient advocate when discussing disability. This study aimed to determine genetic counselors' implicit attitudes toward disability, and identify what factors affect these implicit attitudes. Case scenarios involving disability were used to examine hypothetical estimates of time spent on different topics within a genetic counseling session. Implicit attitudes were measured using the validated Disability Attitudes Implicit Association Test (DA‐IAT), and personal/professional experiences with disability were assessed. Analysis of 382 respondents of the electronic survey revealed that personal experience with individuals with disabilities was not significantly associated with implicit attitudes scores. In addition, results demonstrated that genetic counselors have a stronger bias toward ability ( D mean  = 0.62, D std  = ±0.45) compared to previous participants of the DA‐IAT ( p  < .005). Practice specialty, length of time in the genetic counseling field, or whether the participant was a practicing counselor or genetic counseling student were not associated with implicit attitudes scores. The bias toward ability observed across practice specialties may be due to shared factors that influence interest in this field, but may also potentially reflect the inability of the DA‐IAT to capture the complexity of genetic counselors' relationship to individuals with disability. This study emphasizes the importance of incorporating patients' individual definitions of disability into genetic counseling sessions and building an environment of patient advocacy and education around their personal perspectives and needs.